ANALISA KELAYAKAN INVESTASI JALAN TOL KLBM (KRIAN LEGUNDI BUNDER MANYAR) JAWA TIMUR DENGAN BUILT OPERATE TRANSFER (BOT) MASA KONSENSI - Wiwin Indrayani; Doni Haidar Nur (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
Considering that investment is an effort to allocate funds, in a certain way, to certain assets, so that the owner of the capital will get a return in the form of profits in the future. And, seeing that the construction of the toll road costs a lot of money, this analysis is made to analyze the financial and economic feasibility of the toll road to find out whether the toll road is suitable as a long-term investment or not, with the aim of obtaining optimal investment returns and minimizing or avoiding the unwanted thing is loss. The purpose of this final project is to determine the feasibility of investing in the Krian-Legundi-Bunder-Manyar toll road from an economic and financial perspective. The feasibility analysis is viewed from an economic perspective, which is calculated from the time-saving value and per capita income per day and financial which will be determined based on the value of the benefit cost ratio, internal rate of return and net present value. The method used refers to the data obtained from PT. Waskita Bumi Wira in 2021. From the calculation results, it is found that the Krian-Legundi-Bunder-Manyar toll road is feasible to build. For economic feasibility, the IRR value is 19% and BCR 3,038 and NPV Rp 23,961,865 (in million) for financial feasibility. So that the Krian-Legundi-Bunder-Manyar toll road project is feasible to be an investment. Both from an economic and financial perspective.